Phenology, parasitism and density dependence of Psyllaephagus bliteus on Eucalyptus camaldulensis - Cuello, Eliana Marina; Andorno, Andrea Veronica; Hernandez, Carmen Marcela; Lopez, Silvia Noemi (Springer, 2021)
Glycaspis brimblecombei is an invasive insect species that specifically feeds on Eucalyptus leaves. Native from Australia, this species has spread to several countries becoming a major Eucalyptus pest. Even though its specific endoparasitoid Psyllaephagus bliteus has been present in Argentina since 2005, little is known about its ecology in the region. In this work we assess P. bliteus population development on Eucalypus camaldulensis and identify the meteorological variables associated with changes in its abundance. Furthermore, we study the level of natural parasitism in the field, and the density dependence relationship between P. bliteus and G. brimblecombei. We find that P. bliteus is present throughout the year with a maximum abundance at the end of spring-beginning of summer. Changes in its abundance are associated with temperature and relative humidity although it cannot be ruled out that this is due to an effect of climate on the density of its host. The highest levels of parasitism were registered when psyllid population was minimal, while density dependence analysis detected an inverse relationship between P. bliteus and its host.